PENGEMBANGAN MEDIA PRAKTIKUM HIDROPONIK RAKIT APUNG DAN RASIO NUTRISI YANG BERBEDA UNTUK PERTUMBUHAN SELADA - Rasyati, Dewi; Daningsih, Entin; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed to determine the feasibility of a laboratory work media. The media was design using static and dynamic floating raft hidroponics with different nutrient ratio on subchapter growth and development of living things. The research was Research and Development (R&D), which consisted of six stages namely potential and problems, data collection, product design, design validation, design revision of and limited product trial. This research was modified by adding media validation stages. The validation and student response questionnaires together with student laboratory worksheet were research instruments. Validation was done by media and material expert and categorized as feasible with a pecentage of 100%. Base on the results of the students response questionnaires showed that students strongly agreed with a pecentage of 96.5%. Therefore static and dynamic floating raft hydroponic with different nutrient ratio could be used for a learning laboratory work. Keyword : Laboratory Work, Floating Raft Hydroponic, Feasibility, Student Responses